Inovasi Kedokteran Komunitas Dalam Pelatihan Keselamatan Kerja Di Bidang Pertanian Berbasis Teknologi Melalui Permainan Digital - Tasya Alifia Hanin; Fitria Saftarina; Dewi Nur Fiana (Medula, 2022)
The Occupational Health and Safety sector is currently in training methods to minimize the risk of injury and increase safety at work. Various work sectors have implemented a more active method of delivering training materials, namely through the application of digital games. Digital games are considered successful in some sectors of work, but are limited in agriculture. This is because in the agricultural sector this tends to occur with the same movement and flow. Therefore, this literature aims to understand how to deal with various occupational risks as long as game-based safety in the field can be applied in the agricultural sector. Literature search through Pubmed, Scopus, PsycINFO, and Web of Science with a focus on “serious games” and “gamification” as safety training methods. As a result, digital games that can be applied are through computer technology, with games in the form of increasing levels, points, and challenges being the most popular attraction. During the game, the positive feedback generated and after the game is proven to improve the skills and safety of workers. Therefore, digital games can be developed as an effective, satisfying, and interesting training method for workers in the agricultural sector.